LAND SUITABILITY AND PROBLEMS ASSESSMENT FOR FOOD CROP DEVELOPMENT BASED ON PEDO-AGROCLIMATE AND RESOURCE MANAGEMENT - Aminuddin Mane Kandari; Sumbangan Baja; Ambo Ala; Kaimuddin . (International Journal of Sustainable Tropical Agricultural Sciences (IJSTAS), 2014)
This  study specifically aimed to:  (i) identify of pedo-agroclimate characteristics, (ii) evaluate of  potential avaibility land,  suitability  land  and  problems  for food crops development, (iii) develop planting  and land  recource  management.  This  study was conducted  on  the mainland Buton  Regency, the  used  a spatial analysis method employing GIS.   The study  results showed that: (i) the mainland Buton  regency had relatively varied characteristics of land biophysic. For climate aspects, the region had low and uneven distributed rainfall; (ii)  potential land avaibility for food crops development in study area was : 74,664.64 ha, where the land suitability level of S2 of 5,096.52 ha, S3 of 44,521.38 ha, and the rest was N1 and N2.  The Land suitability classes for crop plant in the study area were: S3 and N1 except for cassava, there were S2, S3, and N. Similar problems were found in almost all areas, i.e. high soil pH >7  -8.5 or low 4 - 4.5, P2O5 content was very low, high air humidity  > 90% or low < 30%, high erosion risk, high slope >15 - 25%, high level of surface rocks >40%, high level of surface layer >40%, very high erosion risk, very high slope >25%), shallow effective dept < 20 cm; (iii) the land resource management, suggested were  improvements: i.e: drainage system, nutrient retention through liming and addition of organic matter for CEC and pH, nutrient availability through liming and fertilization, mechanization potency on slopy area, erosion risk level through reducing erosion rate, making terrace, parallel contour planting, cover crop planting, terrace construction for rice at slopes 3 -8%  and  8 - 15%, water availability through improvement of irrigation system.